1999
DOI: 10.1051/lait:1999434
|View full text |Cite
|
Sign up to set email alerts
|

Raw milk flora affects composition and quality of Bergkäse. 3. Physical and sensory properties, and conclusions.

Abstract: Parallel productions of Austrian Bergkâse from raw or pasteurised milk were perfonned to monitor the effect of heat treatment on physical and sensory properties of the mature cheeses and, in sorne parameters, during ripening. Apart from sorne seasonal variations, analyses of variance showed that neither mechanical properties nor cheese body col our were influenced by the pasteurisation of the milk. However, sensory characterisation of smell and aroma as weil as of the basic taste categories of the mature Bergk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
17
0
2
Order By: Relevance
“…Firmness was the parameter that was most heavily influenced by the season of production resulting in differences in fracture properties. This is consistent with the results obtained by Ginzinger et al [39] for Austrian Bergkäse and may possibly have negative consequences in relation to split defect [69]. The change in firmness of the Emmental with season was attributed to the difference in milk fat composition with increases in liquid proportions in the fat phase of cheese increasing from winter to summer [96].…”
Section: Seasonality Of Milk Supplysupporting
confidence: 90%
See 1 more Smart Citation
“…Firmness was the parameter that was most heavily influenced by the season of production resulting in differences in fracture properties. This is consistent with the results obtained by Ginzinger et al [39] for Austrian Bergkäse and may possibly have negative consequences in relation to split defect [69]. The change in firmness of the Emmental with season was attributed to the difference in milk fat composition with increases in liquid proportions in the fat phase of cheese increasing from winter to summer [96].…”
Section: Seasonality Of Milk Supplysupporting
confidence: 90%
“…Baer and Ryba [4] showed that the influence of raw milk microflora stimulated PAB growth through their proteolytic action, and Beuvier et al [7] reported that cheeses made with raw milk show greater proteolysis and stronger propionic acid fermentation, although other studies have shown no difference in cheese texture between cheeses made from pasteurised and raw milk [9,39]. Further research is required to determine if greater levels of proteolysis and enhanced propionic acid fermentation may promote the occurrence of split defect or secondary fermentation in cheeses made from raw milk in comparison to those made from pasteurised milks.…”
Section: Milkmentioning
confidence: 99%
“…Moreover, previous study on cheese color as a function of ripening time by Rohm and Jaros (1996) reported a decrease for L* value and an increase for a* and b* values during the ripening of Emmental cheese. Ginzinger et al (1999) and Buffa et al (2004) reported that the yellowness index of cheese color highly correlated with the b* value, increasing as cheese ripened and almost corresponded to the sensory difference threshold. Table 3 shows the hue angle and chroma values for the VF and MF cheese samples.…”
Section: Sensory Evaluationmentioning
confidence: 97%
“…At 24 weeks, control sampi es were taken from the second cheese wheel, which was unaffected by any sampling procedure. This procedure was applied because a large amount of chee se was needed for sensory analysis [21], and to obtain evidence whether repeated sampling and the treatment with hot paraffin did affect the composition of the cheeses. Additional samples were taken from the young cheeses after pressing and before brining in order to evaluate the effects of milk pasteurisation (72 "C x 40 s) on basic cornpositional properties.…”
Section: Cheese Production and Samplingmentioning
confidence: 99%